Advancements in nanosensors for cancer detection - Dinesh Bhatia; Tania Acharjee; Monika Bhatia (AIMS Biophysics)
“Faster diagnosis, better outcomes: Biosensors pave the way for a brighter future for cancer patients”. As one of the top causes of death worldwide, cancer must be addressed with the help of innovative treatments and state-of-the-art diagnostic techniques. Due to stress, poor lifestyle choices, and environmental factors, cancer incidence is worryingly on the rise in India, especially among the younger generation. In India, 1 in 5 persons may receive a cancer diagnosis by 2025, potentially impacting 1.57 million people, even though 30–50% of cancers are preventable. Even though standard screening techniques are frequently too costly and impracticable for everyday use, early detection is vital. Alternatives that show promise include emerging biosensor technologies, which give quick, accurate, and customized diagnostic results. Due to its capacity to quickly and automatically identify biological changes, ultra-sensitive biosensing systems utilizing single chips have revolutionized cancer detection. Since they are more effective than conventional techniques, point-of-care (PoC) biosensors—such as innovative nano-sensing devices for exosomal micro-RNA analysis—are becoming increasingly popular. Developing sophisticated diagnostic instruments like bio-computers and resonant mirrors is made easier by these biosensors, which combine analytes, receptors, and electrical sensors to detect cancer biomarkers in biological samples. The accuracy and usability of detection are further improved by advancements in wearable technologies, microfluidics, and electrochemical and graphene-based sensors. BrCyS-Q and NanoLiposomes provide improved photodynamic treatment and targeted medication delivery, respectively. Improved patient outcomes and early intervention are anticipated using the i-Genbox, a colorimetric sensor based on LAMP technology, and DNA-SWCNT-based sensors that further improve biomarker identification for gynecologic tumors.